Institutions and foreign direct investment (FDI) in Malaysia: Empirical evidence using ARDL model - Abdul Karim, Zulkefly; Shah Zaidi, Mohd Azlan; Ismail, Mohd Adib; Abdul Karim, Bakri (2011)
Since 1990’s, institution factors have been regarded as playing important roles in stimulating foreign direct investments (FDI). However, empirical studies on their importance in affecting FDI are still lacking especially for small open economies. This paper attempts to investigate the role of institutions upon the inflow of foreign direct investment (FDI) in a small open economy of Malaysia. Using bounds testing approach (ARDL model), the empirical findings reveal that there exists a long run relationship among FDI and the institution variables.Specifically, several institution variables namely government stability, bureaucracy, and corruption are found to play prominent roles in influencing the inflow of FDI. Thus, in attracting foreign investors, implementing FDI friendly policies by providing and maintaining the quality of domestic institutions would be beneficial to Malaysian economic growth.